Ø§ÙØ®Ø¨Ø± ÙÙ Ø§ÙØ¨ÙØ§ØºØ© Ø§ÙØ¹Ø±Ø¨ÙØ© - Faqihudin, Didin (Hunafa: Jurnal Studia Islamika, 2009)
The science of maâÃ¢nÃ® is a set of rules and of principlesÂ  employed to know how to make an Arabic sentence structure agreeing withÂ  language situation and condition. One of the objects of the science of maâÃ¢nÃ® isÂ  khabar. Khabar isÂ  a sentence that Â may be either true or false, depending on the reality. If the reality agrees with khabar, then Â it is called true khabar, but if not, it is called false khabar. There are two purposes of delivering khabar, namely fÃ¢âidat al-khabar and lÃ¢zim al-fÃ¢âidah. Sometimes the purposes of khabar deviate from that two original purposes to become istirhÃ¢m, izï¬hÃ¢r al-dï¬aâf, izï¬hÃ¢r al-tahassur, etc.Kata Kunci: al-balÃ¢ghah al-âarabiyyah, âilm al-maâÃ¢nÃ®, al-khabar